2009
DOI: 10.1073/pnas.0909361107
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant phosphatidylglycerol inhibits respiratory syncytial virus–induced inflammation and infection

Abstract: Respiratory syncytial virus (RSV) is the most common cause of hospitalization for respiratory tract infection in young children. It is also a significant cause of morbidity and mortality in elderly individuals and in persons with asthma and chronic obstructive pulmonary disease. Currently, no reliable vaccine or simple RSV antiviral therapy is available. Recently, we determined that the minor pulmonary surfactant phospholipid, palmitoyl-oleoyl-phosphatidylglycerol (POPG), could markedly attenuate inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
244
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(252 citation statements)
references
References 39 publications
5
244
1
Order By: Relevance
“…Regarding a potential role of surfactant PGs in anti-inflammatory response, it was observed that Palmitoyl-OleoylPhosphatidylGlycerol (POPG) alone, added to bronchial epithelial cells in culture inhibited interleukin-6 and -8 production, as well as the cytopathic effects induced by Rous Sarcoma Virus infection. Administration of POPG to mice, concomitant with viral infection, almost completely eliminated the recovery of virus from the lungs at 3 and 5 days after infection M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT (58). PG was shown also to inhibit inflammatory responses induced by lipopolysaccharide through direct interactions with the Toll-like receptor 4 (TLR4) interacting proteins CD14 and MD-2 (59).…”
Section: Surfactant Pg In Attenuation Of Pathogen-related Inflammatormentioning
confidence: 99%
“…Regarding a potential role of surfactant PGs in anti-inflammatory response, it was observed that Palmitoyl-OleoylPhosphatidylGlycerol (POPG) alone, added to bronchial epithelial cells in culture inhibited interleukin-6 and -8 production, as well as the cytopathic effects induced by Rous Sarcoma Virus infection. Administration of POPG to mice, concomitant with viral infection, almost completely eliminated the recovery of virus from the lungs at 3 and 5 days after infection M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT (58). PG was shown also to inhibit inflammatory responses induced by lipopolysaccharide through direct interactions with the Toll-like receptor 4 (TLR4) interacting proteins CD14 and MD-2 (59).…”
Section: Surfactant Pg In Attenuation Of Pathogen-related Inflammatormentioning
confidence: 99%
“…However, it can be isomerised to by alveolar macrophages [42]. There is also evidence that PG suppresses proliferation of respiratory viral infection [43,44,45]. Taken together, these data suggest that PG has one or more unique properties that are essential to lung function.…”
Section: Lung Surfactantmentioning
confidence: 62%
“…ToF-SIMS studies have demonstrated that phosphatidylglycerols concentrate along the edges of the tubular proteolipids that form the tubular myelin of pulmonary surfactant and are dispersed throughout the interstitial space between the tubular networks [24]. Of further significance are the observations that phosphatidylglycerols regulate innate immunity against lung viral infections and the associated inflammatory processes [23][24][25][26][27][28][29][30][31]. Recent studies have also demonstrated in murine models that phosphatidylglycerol administration is effective both for postinfection treatment and for prophylaxis against respiratory syncytial viral infections [32], a predominant respiratory pathogen in young children.…”
Section: Discussionmentioning
confidence: 99%